2007
DOI: 10.1063/1.2762279
|View full text |Cite
|
Sign up to set email alerts
|

Mobility enhancement in strained p-InGaSb quantum wells

Abstract: Quantum wells of InGaSb clad by AlGaSb were grown by molecular beam epitaxy. The InGaSb is in compressive strain, resulting in a splitting of the heavy- and light-hole valence bands and an enhancement of the mobility. The mobility was found to increase with increasing InSb mole fraction for values of strain up to 2%. Room-temperature mobilities as high as 1500cm2∕Vs were reached for 7.5nm channels of In0.40Ga0.60Sb. These results are an important step toward the goal of high-performance p-channel field-effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 14 publications
5
76
0
Order By: Relevance
“…Laikhtman et al 7 presented a modeling study of the InGaAs/AlGaAs system with the objective of discussing the critical parameters influencing hole transport. More recently, Bennett et al demonstrated the use of biaxial strain in In x Ga 1-x Sb 8 & GaSb 9 channels to enhance the hole mobility and obtained hole mobilities of greater than 1000cm 2 /Vs at a sheet charge of 1×10 12 /cm 2 . The key concept behind these schemes for enhancing hole mobility is demonstrated in Figure 1, where a narrow bandgap material is inserted between the wide bandgap layers creating a quantum well for the confined holes.…”
Section: Introductionmentioning
confidence: 99%
“…Laikhtman et al 7 presented a modeling study of the InGaAs/AlGaAs system with the objective of discussing the critical parameters influencing hole transport. More recently, Bennett et al demonstrated the use of biaxial strain in In x Ga 1-x Sb 8 & GaSb 9 channels to enhance the hole mobility and obtained hole mobilities of greater than 1000cm 2 /Vs at a sheet charge of 1×10 12 /cm 2 . The key concept behind these schemes for enhancing hole mobility is demonstrated in Figure 1, where a narrow bandgap material is inserted between the wide bandgap layers creating a quantum well for the confined holes.…”
Section: Introductionmentioning
confidence: 99%
“…The HFETs are fabricated using alloyed source/drain ohmic contacts and a Schottky-barrier gate. The growth details of this structure are given in [10]. The device has a source-drain spacing of 3 μm, a gate length of 0.2 μm, and a gate width of 150 μm.…”
Section: Methodsmentioning
confidence: 99%
“…[19][20][21] The biaxial strain in the QWs was previously optimized at 1.8% on GaAs substrates to maximize the hole mobility, 21 and the similar composition of QWs was maintained on the Si substrates.…”
Section: à3mentioning
confidence: 99%